Adjoint-Based Inverse Design of Nanophotonic Structures for Imaging and Sensing Applications - Arfin, Rishad (My University, 2026)
This thesis proposes a systematic and efficient approach to design and optimize different classes of nanophotonic devices for emerging imaging and sensing applications. A computational inverse design approach is used to explore and discover efficient nanophotonic designs in the vast design space, achieving optimal performance. Adjoint sensitivity is highlighted and utilized in the design strategy to accelerate the development and optimization of these devices. The design methodology is demonstrated across several target applications, including complementary metal-oxide-semiconductor (CMOS) microlenses, multispectral metasurface routers for imaging, and metasurface optical sensors for gas and biosensing. The overall results presented in this thesis suggest that inverse design approaches by leveraging adjoint sensitivity provide an efficient way to develop and optimize compact nanostructures, achieving target functionalities for next-generation imaging and sensing applications.
Keywords: Adjoint Sensitivity; Inverse Design; Optimization; Microlenses; Metasurfaces